2016
DOI: 10.1007/s00520-016-3424-7
|View full text |Cite
|
Sign up to set email alerts
|

Axillary web syndrome is not a risk factor for lymphoedema after 10 years of follow-up

Abstract: The occurrence of axillary web syndrome was not a risk factor for lymphoedema after 10 years of follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0
4

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 19 publications
2
19
0
4
Order By: Relevance
“…Knowledge of the pathogenesis of this condition is limited. Current research supports that AWS is caused by a blockage of the normal lymphatic flow as a consequence of the disruption of superficial lymphatics and veins after surgeries such as lymph node biopsy or dissection in patients with breast cancer. We report a nonsurgical case of AWS associated with an epidermal inclusion cyst, which to our knowledge, is the first such case reported.…”
mentioning
confidence: 76%
“…Knowledge of the pathogenesis of this condition is limited. Current research supports that AWS is caused by a blockage of the normal lymphatic flow as a consequence of the disruption of superficial lymphatics and veins after surgeries such as lymph node biopsy or dissection in patients with breast cancer. We report a nonsurgical case of AWS associated with an epidermal inclusion cyst, which to our knowledge, is the first such case reported.…”
mentioning
confidence: 76%
“…Although the initial study to define and describe AWS -a retrospective chart review -reported a frequency of only 6% [4], a 2015 systematic review reported rates ranging from 10 to 85.4% across 6 prospective studies [12]. A prospective cohort study involving 964 breast cancer patients that was published subsequent to that review reported an AWS frequency of 35.9% [11]. This rate is roughly comparable to the median frequency rate for the 17 prospective studies included in the earlier systematic review [12].…”
Section: Prevalence Of Axillary Web Syndromementioning
confidence: 99%
“…Both groups showed significant improvements in quality of life, shoulder flexion strength, arm function, and pain with significantly greater improvements in pain and arm volume reductions for the PT + MLD group [25]. The inclusion of MLD as an intervention and arm volume as an outcome measure is somewhat puzzling, as prospective cohort studies have shown that AWS is not a risk factor for development of lymphedema [9,11].…”
Section: Management Of Axillary Web Syndromementioning
confidence: 99%
“…En el estudio de Wariss et al, se comprobó la relación entre la TLS, y el riesgo de desarrollar LMS en un plazo de seguimiento a diez años. Los resultados del mismo no mostraron relación alguna, concluyendo que la presencia de TLS no se relaciona con el riesgo futuro de desarrollar un LMS (79). Sin embargo, en el International Symposium on Supportive Care in Cáncer, celebrado en Nueva York (2012), se presentó una comunicación acerca de un estudio prospectivo longitudinal a tres años de seguimiento, en el cual las mujeres que desarrollaron TLS presentaron 2,2 veces más LMS que las que no presentaban TLS.…”
Section: Fisiopatologíaunclassified
“…Dicha mujer, durante el tratamiento de la TLS, fue la única que tuvo que ser vendada desde la mano porque se le hinchaba la misma. A pesar de que diversos estudios publicados no establecen relación alguna entre ambas entidades (68,74,79), este resultado coincide con los expuestos por otros autores acerca de la posible relación entre la presencia de TLS y el riesgo futuro de desarrollar LMS, debido a que la primera ya supone una sobrecarga linfática que podría precipitar la segunda (78,80). Sin embargo, siguen siendo necesarios más estudios a largo plazo, con más muestra, para obtener resultados concluyentes.…”
Section: (66)unclassified